Determination of asphalt aging degree: a novel method to determine asphaltene content by centrifugal separation and air stripping technologies. (19th May 2022) - Xiao, Lingfeng; Du, Ruofei; Gong, Lishuhong; Wang, Haidong; Wang, Kang
Abstract: The change of chemical composition of aged asphalt mixture is significant to determine the mechanism of asphalt aging and obtain the direction to produce an advisable asphalt rejuvenator for the specified aged asphalt. For this purpose, this article aims to determine the change of asphaltene after the asphalt aging by centrifugal separation combined with an air stripping method. The result indicates that the content of asphaltene in aged asphalt is approximately 25%, while the content of asphaltene in base asphaltene is about 20%. In addition, compared with traditional distillation-extraction method, the new approach has the advantages of simplicity, rapidity, accuracy and a reduction in pollution to the environment. Furthermore, the analytical result could be provided for preparation and application of asphalt rejuvenators.